Aditivo polimérico derivado de fonte renovável para aplicação em cimento asfáltico de petróleo - Araújo, Fernando de (2016)
This study evaluated the effects of incorporating an additive from an agro-industrial residue, after some chemical modification reactions, to petroleum asphalt cement (CAP) through the polymerization reaction of a viscous polyol obtained by bagasse biomass oxypropylation reaction sugarcane with anhydrides. The polyol is obtained by biomass oxypropylation reaction with propylene oxide, the reaction was performed in an autoclave sealed with pressure and temperature control using 25 mL of OP for every 5 grams of biomass 200°C, which time reaction was two hours. The reaction is revealed by varying the system pressure, initially at atmospheric pressure to reach a maximum pressure value and its subsequent return to atmospheric pressure. For the choice of the most suitable reaction time for polymerization of the polyol with pyromellitic anhydride, the reaction was also conducted in an autoclave sealed with temperature controller (150 ° C) using 20 g of polyol, 1 g of sodium acetate (catalyst) and 8 g of pyromellitic anhydride with the times 30 and 60 minutes. The polymerized materials with different times were characterized by determining the relative viscosity and percentage content of extractable in cyclohexane / ethanol. Given the results with the polymerized material 30 minutes showed the lowest percentage content of extractives and an increased viscosity relative indicating that this time is highlighted with respect to time 60 minutes, because the material is possibly in the form of a crosslinked polymer. Given the choice of time of 30 minutes other polymerization reactions were performed with various anhydrides and other conditions employed different proportions by mass of polyol anhydrides we were referred to as condition I (20 g anhydride and 8 g of polyol), II (20 g anhydride and 20 g of polyol) and III (8 g anhydride and 20 g of polyol). The FTIR spectra of polymeric materials with different polymerization conditions used to prove the occurrence of chemical modification due to the appearance of a characteristic band ester groups (1750 cm-1) present in the polymerized material. He chose to work with the condition III, as is the condition which employs a larger amount of polyol, and even with the smaller amount of anhydride used FTIR spectra revealed that the polymerization reaction was performed. Among the various anhydrides (phthalic, maleic and pyromellitic) of the different conditions used that stood out before the solubility test with solvents analyzed was polymerized material with pyromellitic anhydride because the polymerized material likely in the form of a crosslinked polymer because it was insoluble or poorly soluble in the solvents tested. Polymerization of the polyol with pyromellitic anhydride using condition III, that is, BCPP30, CSPP30, PCPP30 e BCPPG30, provided an increase in thermal stability relative to material in the form of polyol. Applicability tests concerning the incorporation of 16% m / m BCPP30, CSPP30, PCPP30 e BCPPG30 additive in relation to the mass of 600 g CAP showed through characterization tests used, softening point, elastic recovery and marshall dosage, it is possible to use BCPP30 as an additive the conventional CAP, because even with the incorporation of this new additive modified CAP met the specifications of the appropriate standard.